Investigation of Solution Focused-Brief Counseling's effect on reducing the stress levels of college students - Franciskus Rondang Sitindaon; Rahma Widyana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
College students deal with various events that can increase stress levels and negatively impact their lives. The study aimed to investigate the effect of solution-focused brief counseling (SFBC) on reducing college students' stress levels. The hypothesis suggested a decrease after comparing the stress level with SFBC before the intervention. The Participants consisted of 6 active postgraduate psychology students with moderate and high-stress levels. Furthermore, the study used a one-group pretest-posttest design, and the data were obtained through the Stress Scale for College Students (SSCS) and interview. The intervention used SFBC, and was conducted in four meetings. In analyzing the data, the Wilcoxon Signed Ranks Test was used to determine the difference in experimental group values between before and after the intervention. The result showed that there are differences in stress levels before and after the procedure, and its drastic decrease in participants was observed after the intervention.